A Silylene Stabilized by a σ‐Donating Nickel(0) Fragment. (25th May 2022) - Frutos, María; Parvin, Nasrina; Baceiredo, Antoine; Madec, David; Saffon‐Merceron, Nathalie; Branchadell, Vicenç; Kato, Tsuyoshi
Abstract: A donor‐stabilized silylene 4 featuring a Ni 0 ‐based donating ligand was synthesized. Complex 4 exhibits a pyramidalized and nucleophilic Si II center and shows a peculiar behavior due to the cooperative reactivity of Si and Ni centers. Calculations indicate that the orientation of Ni‐ligands with respect to the silylene moiety is crucial in determining the role of the Ni‐fragment (Lewis acid or Lewis base) towards silylene. Indeed, a simple 90° rotation of the Si−Ni bond, reverses the role of Ni, and transforms a classical silylene→Ni 0 complex into an unprecedented Ni 0 →silylene complex. Abstract : A silylene complex stabilized by a Ni 0 ‐based donating ligand was successfully synthesized. This complex exhibits a pyramidalized and nucleophilic Si II atom and shows a peculiar chemical behavior due to the cooperative reactivity of the Si and Ni centers. DFT calculations demonstrated that a simple rotation of 90° on the Si−Ni bond reverses the role of Ni, transforming a classical silylene→Ni 0 complex into the corresponding Ni 0 →silylene complex.